2016
DOI: 10.3390/su8020111
|View full text |Cite
|
Sign up to set email alerts
|

The Making of a Sustainable Wireless City? Mapping Public Wi-Fi Access in Shanghai

Abstract: Abstract:In the context of the global information economy, ready access to the Internet is critical to a city's competitiveness, which has prompted a number of cities to launch plans to establish wireless networks. Most literature on the development of wireless cities focuses on cities in Western countries, and few have discussed how Chinese cities have adopted wireless technologies in their urban infrastructure development efforts. This paper examines recent development and spatial distribution of public Wi-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…Our result is consistent with findings from a recent European Union report [32]. Scientific and technological innovation has been concentrated in the most developed regions, and these regions have become more agglomerated [50,58,59]. …”
Section: The Role Of Internet Access In Regional Developmentsupporting
confidence: 83%
See 1 more Smart Citation
“…Our result is consistent with findings from a recent European Union report [32]. Scientific and technological innovation has been concentrated in the most developed regions, and these regions have become more agglomerated [50,58,59]. …”
Section: The Role Of Internet Access In Regional Developmentsupporting
confidence: 83%
“…Urban residents tend to have higher levels of human capital than non-urban residents [22]. The concepts of the smart city [49] and the wireless city [50], which emphasize that information and communication technologies will play an essential role in city management and public services, have recently attracted considerable attention from scholars and policymakers.…”
Section: Internet Spillover and Its Complexitymentioning
confidence: 99%
“…Increasing attention has been paid to urban inequalities, and studies have found that Chinese cities have become more unequal. New urban problems similar to those found in the United States are also emerging, such as residential segregation, spatial mismatch, and digital divide, with high inequalities of housing, education, and health (see Wang and others ). The distribution of high‐quality public resources is also highly uneven within cities, as they are often concentrated in city centers and, to a lesser extent, newly developed subcenters.…”
Section: Spatial Inequality In Chinamentioning
confidence: 91%
“…Wang et al examine Shanghai's adoption of wireless technologies in urban and infrastructure development and the spatial distribution of public Wi-Fi access in Shanghai [45]. By mapping both government-sponsored hotspots through the "i-Shanghai" project and the hotspots established by China Mobile Communications Corporation (CMCC), they find that Shanghai's telecommunication providers have been proactive in arranging WLAN hotspots (a proxy of public Wi-Fi or wireless access).…”
Section: New Dimensions Of Urban Land Use and Urban Spacementioning
confidence: 99%